Effect of topical magnesium sulfate on labor duration and childbirth experience: a randomized controlled trial - Sahar Rouhzendeh; Sanaz Mousavi; Mojgan Mirghafourvand; Sakineh Mohammad-Al (BMC, 2024)
Abstract Background Magnesium sulfate is used topically to reduce the duration of labor in some regions of the country. However, there is insufficient evidence about its effectiveness. This study aimed to determine whether topical magnesium sulfate reduces labor duration and improves childbirth experience (primary outcomes). Methods In this randomized controlled trial, the participants were 98 women with low-risk, singleton, and full-term pregnancies admitted to a teaching hospital in Iran. They were randomly assigned to the intervention group (receiving 50% magnesium sulfate) or the control group (receiving distilled water) stratified by parity and onset of labor. The participants, interventionists, and data collectors were blinded. During the vaginal examination at the beginning of the active phase of labor, 10 mL of magnesium sulfate or distilled water was poured on the cervix of the uterus. Data collection was performed by the researcher with continuous monitoring up to two hours post-delivery and follow-up at 4-5 weeks postpartum. The Childbirth Experience Questionnaire 2.0 was used to examine childbirth experience. We performed a modified intention-to-treat analysis, excluding those whose outcome of interest could not be assessed. Independent-samples t-tests were used to compare the groups in terms of the mean of the primary outcomes. Results Participant recruitment took place between December 2021 and December 2022. Thirty-three percent were primiparous and 37% had induced labor. Three women in the intervention group and seven in the control group underwent emergency cesarean sections. All 49 women assigned to each group were included in the analysis of labor duration outcome, while one and two women were excluded from the analysis of childbirth experience score due to loss to follow-up. In the intervention group, compared to the control group, the mean duration of the intervention until delivery was significantly shorter (1.59 vs. 2.93 h; MD -1.34, 95% CI [-1.88 to -0.79]) and the childbirth experience score was higher (3.1 vs. 2.3, MD 0.84; 95% CI [0.59 to 1.08]). Conclusions According to the results of this trial, pouring 10 mL of 50% magnesium sulfate on the cervix at the beginning of the active phase of labor probably reduces labor duration and improves the childbirth experience. Trial registration Ethics Committee of Tabriz University of Medical Sciences: IR.TBZMED.REC. 1400.726. Iranian Registry of Clinical Trials: IRCT20100414003706N40 Registration date: 21/11/2021 ( https://en.irct.ir/trial/58323 ).